Medium energy charged particle detector with a deflecting electrostatic field for measurement of suprathermal electrons, protons, and neutrals aboard next-generation small satellite-1. Issue 4 (15th August 2021) - Seo, Hoonkyu; Shin, Yuchul; Woo, Ju; Seol, Woohyung; Lee, Chaean; Lee, Chanhaeng; Lee, Hyunsang; Seon, Jongho; Sohn, Jongdae; Min, Kyoungwook; Ryu, Kwangsun; Shin, Goohwan; et al.
Highlights: Development, testing, and early operation result of a space instrument are presented. The instrument can measure and identify charged particles and neutrals in 20–400 keV with a 6.25 keV resolution. Test results of the flight model instrument against laboratory radioisotopes are provided. Results from a numerical simulation to estimate the instrument's performance are discussed. The instrument capabilities are successfully demonstrated in low-earth orbits. Abstract: This paper presents the development, testing, and early operation of a space-borne instrument that can measure and identify charged particles and neutrals in the energy range of 20–400 keV with a 6.25 keV energy resolution. The instrument generates electric fields perpendicular to its entrance aperture, which allows it to identify electrons, ions, and neutrals by deflecting the trajectories of charged particles along the direction of the electric fields. Four identical detector pixels with thin windows, relatively positioned along the direction of the electric fields, independently measure each energy distribution of particles with a total geometric factor of approximately 0.01 cm 2 ·sr. In addition, to measure higher particle fluxes, up to 10 9 /(cm 2 ∙sr∙s), a reduction in particle fluxes by a factor of ∼100 is possible with a mechanical attenuator. Two identical telescopes, each with a field-of-view of 15° × 70°, are orthogonally placed to measure particles with different pitch angles relative to local magnetic fields. The test results of the flight model instrument against laboratory radioisotopes, 241 Am, 133 Ba, and 14 C, are provided, together with results from a numerical simulation to estimate the instrument's performance. The instrument capabilities are successfully demonstrated with energy spectra of particle distributions acquired from in-orbit operations.